Study on the optimization of surface modification processing of SiCp and tribological properties of AA6061-SiCp based composites - Odiwo, Hammed; Kamilu Adeyemi, Bello; Malik, Abdulwahab; Abdulmumin Adetayo, Adebisi; Umma, Abdullahi; Mamuda, Dodo Rayyan; Maleque, Md. Abdul; Muhammad Uhuotu, Suleiman (Deer Hill Publications, 2023)
The unique property combination of Al/SiCp based composites make them very attractive for applications in automotive and aerospace industries. The choice of composite materials for these applications is directly influenced by their inherent properties which are a function of the processing route employed. Like other processing parameters, surface modification treatment of SiCp can play a major role in determining the properties of Al/SiCp composites. In this study, the effects of SiC reinforcement (wt%) fractions (SRF), surface oxidation temperature (SOT) and preheating temperature (PT) parameters on the wear and friction properties of stir-cast Al-SiCp based composite were investigated. Experimental data and models are generated and analyzed based on a three-factors-five-level central composite design (CCD) and analysis of variance (ANOVA). The empirical models developed for wear rate and coefficient of friction (COF) considering the pre-processing parameters adequately predicts the Al-SiCp properties with the silicon carbide reinforcement (wt%) fraction emerged as the most influencing factor. The goal of the optimization process is to minimize both wear rate and COF. For wear rate, SRF at 44.49 % contribution had the most influence on wear rate, while SOT and PT had 0.65 % and 1.03 % influence on wear rate respectively. For COF, SRF also showed highest influence of 35.48 % on COF, while SOT and PT had 0.047% and 2.66% influence on COF respectively. From the optimization analysis, the set of conditions that simultaneously optimizes both wear rate and COF are 10% SiC weight (SW), 1234°C surface oxidation temperature (SOT), and 376.2°C preheat temperature (PT). The resulting responses at this optimized condition are minimum wear rate of 0.11 mm3 /m and COF of 0.11 with a confidence and desirability level of 1.